The competent vocational college teacher: a proposed model for effective job performance - Arifin, Muhammad Aiman; Mohd Rasdi, Roziah (Human Resource Management Academic Research Society, 2017)
Technical Vocational Education and Training (TVET) have been strategized as the main route to supply skilled worker as to achieve the developed nation status by 2020. In 2012, Transformation of vocational school to vocational college (VC) was the biggest shifted in history by the Malaysian government under the area vocational education. The objectives are to prepare students with the combination of vocational theory and skills, entrepreneurship as well as employability. In view of globalization, knowledge economy, technology advances and global labor mobility requires vocational college teachers to practically competent and effective in profession. Therefore, the model presented was proposed for vocational college teachers based on the needs and importance competencies for effective job performance also the demands from 21st century world of work.